Cecílio: um chatbot para automação do atendimento aos usuários em Instituições Federais de Ensino Superior - Feitoza, Felipe Ramos (2021)
In view of the unprecedented changes in social life caused by the COVID-19 pandemic, the organizations have faced the reality of having their products and services distanced from their users. As a result of the advances made possible by Artificial Intelligence, chatbots have become strategic tools for Brazilian companies to strengthen their service capacities. Public Administration Entities not being immune to the consequences of the threat suffered need to be, principles governing its activities, implement reformulations in the provision of the services offered to the society, to avoid harm in meeting the needs of citizens. The general objective of this study was to map and analyze the Public Service Process at the Direction of the Center for Humanities, Letters and Arts of the Federal University of Paraíba and present a proposal for the automation of part of the steps carried out by the Executive Secretariat through the choice of one of the platforms available in the market for the development of Chatbot Cecílio, a Virtual Conversation Assistant to be shared on the Teaching Center Website to present through decision trees the alternatives to meet the needs of users. As specific objectives were foreseen and achieved: to identify the critical factors in the execution of the service provided to users of the Teaching Center Direction; design a new service flow taking advantage of the improvement opportunities to be detected; establish criteria for rational choice of platform; and define the indicators for monitoring and evaluating the virtual execution of customer service. Documents with requests received by the Executive Secretariat, studied from the perspective of the bibliographic sources researched, allowed the construction of the new workflow, from the analysis of the process made possible by the techniques of the Ishikawa Diagram and GUT Matrix. Supportes by the Operational Research, a Multicriteria Analysis was carried out, which resulted in the rational choice of the NEORON platform. Once the objectives have been fulfilled, the automated execution of the service by Cecílio provides the following results: to users, higher quality and satisfaction; to Technical-Administrative Education Servers of the Executive Secretariat, development and professional improvement; and to Direction of the Teaching Center, better management of the process for its continuous improvement.